1975
DOI: 10.1038/hdy.1975.49
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the environmental sensitivity of selection lines by the selection environment

Abstract: SUMMARYThe parents chosen to continue 10 independent selection lines of Sc/zizophyllurn commune over eight successive generations of selection, along with unselected controls, have been retrospectively examined for their response to growth at 15°, 20°, 25°, 30° and 35°C. The regression of rate of growth on temperature was essentially linear over the range 15° to 30°C for all lines irs all generations as was also the regression of rate of growth on various biological assessments of the environments over the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 3 publications
7
21
0
Order By: Relevance
“…The data presented are in good agreement with the model proposed by Jinks & Connolly (1975) and validated by Jinks & Pooni (1982) in Nicotiana rustica. Our study is only a partial test of the model as genotypes selected for low grain yield in both low or high yielding conditions were not available.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The data presented are in good agreement with the model proposed by Jinks & Connolly (1975) and validated by Jinks & Pooni (1982) in Nicotiana rustica. Our study is only a partial test of the model as genotypes selected for low grain yield in both low or high yielding conditions were not available.…”
Section: Discussionsupporting
confidence: 78%
“…Jinks & Pooni (1982) reported that the relationship between selection environment and environmental sensitivity for final plant height in Nicotiana rustica is in agreement with the model. Crossa et al (1989) found that maize varieties selected for average performance across sites were not necessarily more stable than varieties selected for performance at specific sites.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Thus in Nicotiana rustica, JINKS and his co-workers (JINKS et al ., 1977 ;JINKS & POONI, 1982) have been able to establish lines with all combinations of high and low mean performance for flowering time and plant height with high and low sensitivity to environmental change, namely season or sowing date . Similarly, in Schizophyllum JINKS & CONNOLLY (1975) were able to select for differing growth rates in response to differing temperature regimes . From their studies they identified a number of situations under which selection should take place in order to achieve any desired combination of mean performance and sensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…Examples are yield in maize (Eberhart and Russell, 1966) and final height in Nicotiana rustica (Jinks and Connolly, 1975). The present study was conducted on spring barley to assess the linear regression approach as a means of measuring a genotype's environmental sensitivity.…”
Section: Introductionmentioning
confidence: 99%